Wind loading of structures. - Holmes, John D., 1942-; Bekele, Seifu (Boca Raton : CRC Press, 2020)
Wind forces from extreme wind events are the dominant loading for many parts of the world, exacerbated by climate change and the continued construction of tall buildings and structures. This authoritative source, for practising and academic structural engineers and graduate students, ties the principles of wind loads on structures to the relevant aspects of meteorology, bluff-body aerodynamics, probability and statistics, and structural dynamics. This new edition covers: Climate change effects on extreme winds - particularly those from tropical cyclones, hurricanes and typhoons Modelling of potential wind vulnerability and damage Developments in extreme value probability analysis of extreme wind speeds and directions Explanation of the difference between return period' and average recurrence interval', as well as bootstrapping' techniques for deriving confidence limits Wind over water, and profiles and turbulence in non-synoptic winds An expanded chapter on internal pressures produced by wind for various opening and permeability scenarios Aerodynamic shaping of high- and low-rise buildings Recent developments in five major wind codes and standards A new chapter on computational fluid dynamics (CFD), as applied to wind engineering A greatly expanded appendix providing the basic information on extreme wind climates for over 140 countries and territories Additional examples for many chapters in this book
OCLC-licensed vendor bibliographic record.
Keywords: Wind-pressure.; TECHNOLOGY / Engineering / Civil